Expression of TRPM2 ion channels with histopathological alterations following brain ischemia-reperfusion injury in rats - Balgetir, F.; Demir, C.; Kuloglu, T.; Gonen, M.; Aytac, E.; Bulut, S. (Wiley, 2016)
[Abstract Not Available]